Cortical Surface Spatial Analysis Reveals Altered Brain Functional Network Topology in T2DM With Mild Cognitive Impairment - YanJun fan; Jing Tian; XiaoMei Yu; Chen Yang; HuiYan Zhang; Jian Tan; YiWei Zhao; Jing Wei; Gang Huang; JiangPing Liu; LianPing Zhao (Brain and Behavior)
ABSTRACT Objective Approximately 45.0% of patients who have type 2 diabetes mellitus (T2DM) exhibit mild cognitive impairment (MCI). However, the specific alternations in T2DM with MCI (T2DM‐MCI)‐related brain functional networks (BFN) remain unclear. Therefore, the present study aimed to investigate the alterations in the topological properties of BFN in T2DM patients with and without MCI, utilizing a cortical surface‐based graph theory analysis of resting‐state functional magnetic resonance imaging data. Methods Neuropsychological performance and topological properties of BFNs were determined in 64 T2DM‐MCI patients, 58 T2DM patients without MCI (T2DM‐noMCI), and 78 healthy controls (HC). Moreover, we conducted the correlation and stepwise multiple linear regression analysis. Results The T2DM‐MCI group showed increased global efficiency and decreased shortest path length compared to T2DM‐noMCI. In the left posterior cingulate, the T2DM‐MCI group exhibited higher nodal efficiency compared to the T2DM‐noMCI group. Additionally, both degree centrality and nodal efficiency in the T2DM‐noMCI group were significantly lower than in the HC. Degree centrality and nodal efficiency in the left basal ganglia were elevated in both T2DM groups. Alterations in these regions were related to cognitive function scores. Conclusion The alterations in nodal properties of the left basal ganglia suggest that nodal attributes in this region may be involved in the neurophysiopathological mechanisms of brain injury in T2DM. Conversely, the alterations of nodal efficiency in the left posterior cingulate gyrus indicate its potential as a neuroimaging biomarker of cognitive impairment in T2DM patients.